Emergence of blaNDM-5 and blaOXA-232 Positive Colistin- and Carbapenem-Resistant Klebsiella pneumoniae in a Bulgarian Hospital - Rumyana Markovska; Petya Stankova; Georgi Popivanov; Ivanka Gergova; Kalina Mihova; Ventsislav Mutafchiyski; Lyudmila Boyanova (MDPI AG, 2024)
The rapid spread of carbapenemase-producing strains has led to increased levels of resistance among Gram-negative bacteria, especially enterobacteria. The current study aimed to collect and genetically characterize the colistin- and carbapenem-resistant isolates, obtained in one of the biggest hospitals (Military Medical Academy) in Sofia, Bulgaria. Clonal relatedness was detected by RAPD and MLST. Carbapenemases, ESBLs, and mgrB were investigated by PCR amplification and sequencing, replicon typing, and 16S rRNA methyltransferases with PCRs. Fourteen colistin- and carbapenem-resistant K. pneumoniae isolates were detected over five months. Six carbapenem-resistant and colistin-susceptible isolates were also included. The current work revealed a complete change in the spectrum of carbapenemases in Bulgaria. blaNDM-5 was the only NDM variant, and it was always combined with blaOXA-232. The coexistence of blaOXA-232 and blaNDM-5 was observed in 10/14 (72%) of colistin- and carbapenem-resistant K. pneumoniae isolates and three colistin-susceptible isolates. All blaNDM-5- and blaOXA-232-positive isolates belonged to the ST6260 (ST101-like) MLST type. They showed great mgrB variability and had a higher mortality rate. In addition, we observed blaOXA-232 ST14 isolates and KPC-2-producing ST101, ST16, and ST258 isolates. The colistin- and carbapenem-resistant isolates were susceptible only to cefiderocol for blaNDM-5- and blaOXA-232-positive isolates and to cefiderocol and ceftazidime/avibactam for blaOXA-232- or blaKPC-2-positive isolates. All blaOXA-232-positive isolates carried rmtB methylase and the colE replicon type. The extremely limited choice of appropriate treatment for patients infected with such isolates and their faster distribution highlight the need for urgent measures to control this situation.